Varieties of Tone - Kortum, R. author. aut Link
XV, 258 p.
Keywords: In clear and lively prose that avoids jargon, the author carefully and systematically examines the many kinds of subtly nuanced words or word-pairs of everyday discourse such as 'and'-'but', 'before'-'ere', 'Chinese'-'Chink', and 'sweat'-'perspiration', that have proven resistant to truth-conditional explanations of meaning.